Elektrostatski elektronski spektrometer za merjenje Augerjevih spektrov v plinih - Pelicon, Primož (Vakuumist, 1996)
Electron spectrometer for gas-phase targets was built at the Dept. for low and medium energy physics of the "Jožef Stefan" Institute. The processes wthinthe inner atomic shells, wich are objects of the investigations, are briefly described. The electrons from interaction centre are focused by three-element electrostatic lens of rectangular shape and injected into planparallel electrostaic analyser. We present some details of the mechanical adjustment and working features of the spectrometer.
Keywords: atomska fizika; spetrometri; meritve; vakuumski sistemi; plini